A Novel PLC Front-haul for 5G IoT Indoor Communication using Split C-RAN Architecture - Ibrahim, Mai (University of Waterloo, 2024)
The demand for efficient telecommunications in the era of Fifth Generation (5G) and Internet of Things (IoT) necessitates innovative approaches to network architecture and communication technologies. Recently, split Centralized Radio Access Network (C-RAN) architecture, characterized by Central Unit (CU), geographically dispersed Distributed Unit (DU), and indoor Radio Units (RUs), has presented opportunities for optimizing communication links in indoor environments. Yet, the adaptation of this innovative architecture to enable massive indoor IoT applications is still deemed inefficient due to the associated cost of deployment. Accordingly, this research investigates Power-Line Communication (PLC) as a cost-efficient alternative solution for C-RAN front-haul. Specifically, the focus is on exploring the utilization of indoor low-voltage power lines in the context of 5G New Radio (NR) indoor IoT applications. First, to ensure that standard protocols like Common Public Radio Interface (CPRI) and Enhanced Common Public Radio Interface (eCPRI) can run on PLC, we introduce two novel patented components to the architecture, namely the CPRI-PLC-Gateway (CPG) and Enhanced CPRI-PLC-Gateway (eCPG). These are a plug and play components that come in pairs. They are used to create a virtual PLC front-haul link ensuring transparent transportation of unmodified CPRI or eCPRI frames between DU and RUs, even under challenging PLC channel conditions. As such, they set the foundation for optimizing the PLC front-haul and help resolve various challenges, including PLC time-varying nature and susceptibility to additive white Gaussian noise (AWGN). Furthermore, investigations are extended to study the impact of the proposed PLC based split C-RAN system in the context of the Radio access network (RAN). For that, an indoor multi-story service building that houses a large number of air-interfaced IoT devices is considered. To ensure that the reported results apply to real-life applications, we consider a PLC network that encompasses typical indoor low-voltage 3-phase power lines and follows TN-S earthing configuration. Accordingly, it is shown that through the incorporation of the CPG and eCPG components, the implementation of In-band full-duplex (IBFD) communication over the multiple Input - multiple output (MIMO) PLC channel, and the integration of the hybrid circuit-based isolation, the system can support a considerable number of air interfaced IoT devices at standardized rates. It is also shown that the self-interference over the power line segment is mitigated which ensures robust bidirectional communication in the system. Moreover, a significant aspect of the thesis revolves around conducting a comprehensive performance analysis for the proposed PLC front-haul for IoT indoor communications. Mathematical models, rooted in queuing theory, Markov modelling, and stochastic geometry, are developed to assess the end-to-end delay performance of the indoor front-haul solution. Analytical expressions are derived for various performance metrics, including radio coverage probability, the number of served devices, and system delay. Wireless spatial models, path-loss models, and interference considerations are meticulously analysed in terms of multiple factors such as the number of wireless IoT devices, radio and PLC bandwidth, and transmission technology, in regard to the delay performance of the proposed system. These models are rigorously validated through extensive simulations, demonstrating compliance with stringent 5G, CPRI, and eCPRI bit error rate (BER) and delay requirements. Last, as the thesis further aims to examine the optimization challenge of maximizing throughput in a split-RAN system that includes a PLC front-haul link within a multi-story building. The goal is to optimize the number of fulfilled IoT devices while simultaneously satisfying their quality of service (QoS) criteria. The optimization problem is defined as a mixed-integer non-convex problem, which includes several objectives: maximizing the number of satisfied devices, minimizing operating cost, minimizing device transmit power, and minimizing PLC access delay. The thesis further explores the application of an Evolutionary Multi Objective Optimization (EMO) algorithm, specifically Non-dominated Sorting Genetic Algorithm II (NSGA-II), to address the issue of conflicting objectives in communication systems. The method operates by systematically generating successive iterations of solutions using tournament selection, single-point binary and simulated binary crossovers, and polynomial mutation operators. The system outcomes present a Pareto front consisting of non-dominated solutions for the issue defined using multi-objective optimization (MOO) showing a trade-off between the system objectives.
Keywords: Massive Machine type communication (mMTC); Internet of things (IoT); Power Line communications (PLC); Evolutionary Multi-objective Optimization Problem (EMO); Non-dominated Sorting Genetic Algorithm II (NSGA-II); Stochastic geometry; Hybrid automatic repeated request (HARQ); Impulsive noise detection; 5G New Radio; Centralized radio access network (C-RAN); CPRI; eCPRI